1974
DOI: 10.1111/j.1365-2044.1974.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral table tilt for Caesarean section

Abstract: The deleterious effects on maternal haemodynamics of inferior vena-caval compression by the gravid uterus are well e~tablished.'-~ The resultant decrease in cardiac output may constitute a threat to both mother' and f~e t u s .~-~ These problems may be alleviated by lateral displacement of the uterus,'", by tilting the patient with a wedge," or by operating in the left lateral position.'3 Lateral table tilt may be advantageous for Caesarean section using spinal analgesia, but results appear less conclusive und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several studies resulted in the 15° tilt recommendation that has survived to this day. [9][10][11] However, this conclusion has also been questioned. 7,8,12 In particular, Lee et al 12 performed an RCT of the 15° left-sided tilt and supine positions under spinal anesthesia.…”
mentioning
confidence: 99%
“…Several studies resulted in the 15° tilt recommendation that has survived to this day. [9][10][11] However, this conclusion has also been questioned. 7,8,12 In particular, Lee et al 12 performed an RCT of the 15° left-sided tilt and supine positions under spinal anesthesia.…”
mentioning
confidence: 99%
“…There was a less marked increase in maternal metabolic acidosis and more efficient foetal oxygenation. Downing et al (1974) confirmed the benefits to the foetus of displacement of the gravid uterus from the aorta and vena cava. Uterine displacement, from evidence cited, should therefore be mandatory in the last trimester.…”
Section: Stagnant Hypoxiamentioning
confidence: 61%
“…In 1970-1974, it was demonstrated that 15° left lateral tilt during cesarean section improved fetal pH [95][96][97] . However, recent studies using magnetic resonance imaging showed that the inferior vena cava was completely compressed in both the supine and 15° left lateral tilt position, while 30° left lateral tilt position partially relieved the compression 98,99 .…”
Section: Hemodynamicsmentioning
confidence: 99%